Retrospective Analysis of the Conceptual Model of Economic Management in Sub-regional Structures - Litvinenko, Inna L.; Lobova, Svetlana V.; Gurieva, Lira K.; Kamberdiyeva, Svetlana S.; Mokrushin, Alexandr A. (International Journal of Economics and Financial Issues, 2016)
Modern Russian model of building a system of economic management sub-localities based on the provisions of the Federal Law â„–131-FZ of 06.10.2003 “On general principles of local self-government in the Russian Federation”. Terms and conditions of formation of the system of local government in Russia since the beginning of the reform of its political system and establishment of a model of mutual relations of the state and local levels of government are associated with a rigid opposition rival power elite. On the basis of generalization of foreign practice of granting local governments a certain jurisdiction may be concluded that most of the issues at the local level, if we abstract from their purely legal understanding, are public in nature. Based on the research practice of interaction of bodies of state power and local self-government bodies authors consider it possible to state that the municipal authority has a number of features inherent in the government: a distinct institutionalized character; Time continuity, flexibility, universality; on the basis of laws and other regulations; implementation in a particular area in relation to all individuals within its entities; the possibility of using funds of legitimate violence; the establishment and collection of taxes; independent budgeting. Keywords: region, economic management model, sub-regional structures JEL Classifications: P5, R10, R58